Effects of drugs on the accumulation and spontaneous release of noradrenaline in the rat anococcygeus muscle. - Doggrell, S A (1978)
1 The ability of drugs to inhibit noradrenaline accumulation and to release noradrenaline was studied in the isolated anococcygeus muscle of the rat. 2 Noradrenaline, tyramine, 2-amino,6,7-dihydroxy-1,2,3,4-tetrahydronaphthalene (ADTN), 2-amino,6,7-dimethoxy-1,2,3,4-tetrahydronaphthalene (dimethyl ADTN), and 5-hydroxytryptamine were all potent inhibitors of noradrenaline accumulation and potent releasers of noradrenaline. ADTN was accumulated by the rat isolated anococcygeus muscle. 3 Amphetamine and desipramine were potent inhibitors of noradrenaline accumulation but poor releasers of noradrenaline. 4 Methoxamine, oxymetazoline, acetylcholine, and angiotensin were poor inhibitors of noradrenaline accumulation and did not release noradrenaline. 5 The mechanism of action of these drugs is discussed.